Information literacy skills are required in finding reliable toxicological information resources (Journal of EAHIL, 2021)
Chemicals are a part of modern life, but they are potentially hazardous. Consumers, regulatory authorities, information specialists, researchers, students, and toxicologists need access to evidence-based safety information about chemicals either in their ordinary life or in their work to protect their own health, that of other co-workers and ultimately the environment in which we all live. The most important open sources of safety information are databases such as PubMed and PubChem and open access scholarly journals, as well as websites of regulatory authorities and research institutions. This paper discusses the need for toxicological information literacy and its contents for all to identify reliable information. Reliable open access sources for toxicological information of chemicals are also provided.